Convexity of Certain q-Integral Operators of p-Valent Functions - Selvakumaran, K. A.; Purohit, S. D.; Secer, Aydin; Bayram, Andmustafa (HINDAWI LTD, 2014)
By applying the concept (and theory) of fractional q-calculus, we first define and introduce two new q-integral operators for certain analytic functions defined in the unit disc u. Convexity properties of these q-integral operators on some classes of analytic functions defined by a linear multiplier fractional q-differintegral operator are studied. Special cases of the main results are also mentioned.
Keywords: SUBCLASSES; Mathematics